2008
DOI: 10.1590/s0101-81752008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Nest deprivation and mating success in Nile tilapia (Teleostei: Cichlidae)

Abstract: We tested the effect of nest deprivation on the mating success and sexual selection of dominant Nile tilapia males in two treatments, consisting of two males and three females kept on aquarium with or without nesting substrate (INS: with substrate inside, N = 9; NOS: non-substrate inside, N = 11). Other male traits potentially affecting mating success, such as aggressiveness level, courtship investment, and condition factor were also analyzed. The dominant male's behavior was video-recorded in four 20-min sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…A similar effect was described by Mendonc¸a et al (2010), who reported that male O. niloticus visited different substrata (sand, shell, stones and glass) at similar rates, but nested preferentially on sand. As this kind of excavation (nesting) is used by O. niloticus for attracting females and laying eggs (Mendonc¸a and Gonc¸alves-de-Freitas, 2008), Mendonc¸a et al (2010) concluded that preferential nesting on sand indicates that the male Nile tilapia reproductive condition affects the choice of substratum type. In the present study the fish reproductive condition was not evaluated; however, 14 of 15 fish dug one type of river substratum, a reproductive behavior usually associated with reproductive status.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A similar effect was described by Mendonc¸a et al (2010), who reported that male O. niloticus visited different substrata (sand, shell, stones and glass) at similar rates, but nested preferentially on sand. As this kind of excavation (nesting) is used by O. niloticus for attracting females and laying eggs (Mendonc¸a and Gonc¸alves-de-Freitas, 2008), Mendonc¸a et al (2010) concluded that preferential nesting on sand indicates that the male Nile tilapia reproductive condition affects the choice of substratum type. In the present study the fish reproductive condition was not evaluated; however, 14 of 15 fish dug one type of river substratum, a reproductive behavior usually associated with reproductive status.…”
Section: Discussionsupporting
confidence: 85%
“…(), who reported that male O. niloticus visited different substrata (sand, shell, stones and glass) at similar rates, but nested preferentially on sand. As this kind of excavation (nesting) is used by O. niloticus for attracting females and laying eggs (Mendonça and Gonçalves‐de‐Freitas, ), Mendonça et al. () concluded that preferential nesting on sand indicates that the male Nile tilapia reproductive condition affects the choice of substratum type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduction can take place even in the absence of nest (27). Thus, the environmental structure of the present study might have stimulated females to build nest.…”
Section: Discussionmentioning
confidence: 87%
“…Fish position was registered based on the placement of the fish's eye inside the substratum quadrant. A nest was defined as an excavated area in any of the three substrata sufficient to allow nesting, as previously described (Mendonça & Gonçalves‐de‐Freitas, 2008). As male position could be influenced by female location, the position of both males and females was analysed.…”
mentioning
confidence: 99%